Inside Cover: Photodissociation and Dissociative Photoionization Mass Spectrometry of Proteins and Noncovalent Protein–Ligand Complexes (Angew. Chem. Int. Ed. 32/2013). Issue 32 (26th July 2013) - Canon, Francis; Milosavljević, Aleksandar R.; van der Rest, Guillaume; Réfrégiers, Matthieu; Nahon, Laurent; Sarni‐Manchado, Pascale; Cheynier, Véronique; Giuliani, Alexandre
<x xml:space="preserve">Abstract</x> Identification of the noncovalent binding sites of an intrinsically disordered protein is a challenge. In their Communication on page 8377 ff., A. Giuliani and co‐workers use synchrotron radiation coupled to mass spectrometry to perform photo‐fragmentation of a human intrinsically disordered protein. The interaction of the protein with tannins is involved in the perception of astringency upon drinking tea or red wine. The method maintains the noncovalent bonds, allowing the identification of the protein tannin binding site.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>